2007
DOI: 10.1590/s1415-47572007000600021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in a closed line of the white shrimp Litopenaeus vannamei (Penaeidae)

Abstract: The culture of the marine shrimp Litopenaeus vannamei has recently boosted the Brazilian shrimp industry. However, it is well known that selection methods based solely on phenotypic characteristics, a reduced number of breeders and the practice of inbreeding may promote a significant raise in the genetic similarity of the captive populations, leading to greater disease susceptibility and impairing both the growth and final size of the shrimps. We used four microsatellite loci to investigate genetic variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The specific loci were selected from the literature as the most highly diverse for this species (Cruz et al 2002(Cruz et al , 2004Valles-Jiménez et al 2005;Machado-Tamayo 2006;Garcia and Alcivar-Waren 2007;Luvesuto et al 2007). We had 6 and 4 % reduction of H o in Amiri-Gomishan (0.479-0.450) and Amiri-Gorgeaj (0.479-0.458) populations that represent a 5.4 and 3.6 % increase in inbreeding, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The specific loci were selected from the literature as the most highly diverse for this species (Cruz et al 2002(Cruz et al , 2004Valles-Jiménez et al 2005;Machado-Tamayo 2006;Garcia and Alcivar-Waren 2007;Luvesuto et al 2007). We had 6 and 4 % reduction of H o in Amiri-Gomishan (0.479-0.450) and Amiri-Gorgeaj (0.479-0.458) populations that represent a 5.4 and 3.6 % increase in inbreeding, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using microsatellites, Lima et al (2008) reported F IS ranging from 013 to 0.39 in L. vannamei from Bahia State (Northeastern Brazil). Other studies conducted with L. vannamei populations from Brazilian post-larvae production laboratories showed F IS ranging from 0.00 to 0.38 (Luvesuto et al, 2007;Lima et al, 2010;Maggioni et al, 2013). Considering the history of geographical isolation, the higher F IS values observed in populations Lv-A and Lv-B from Southern Brazil are likely related to inbreeding.…”
Section: Discussionmentioning
confidence: 78%
“…Reductions in genetic variation as time under culture have increased have been reported in P. japonicus (Sbordoni et al 1986(Sbordoni et al , 1987, P. chinensis (He et al 2004;Li et al 2006b), P. stylirostris (Bierne et al 2000;Goyard et al 2003) and P. vannamei ), but the decrease over time is highly variable, with many populations held for more generations showing less loss than populations held for less time . No decline over time was observed for stocks of P. chinensis (Zhang et al 2004) or P. vannamei (Cruz et al 2004;Soto-Hernandez & Grijalva-Chon 2004;Luvesto et al 2007).…”
Section: Domesticated Stocks and Genetically Improved Strainsmentioning
confidence: 99%